Prior viral infection primes cross-reactive CD8+ T cells that respond to mouse heart allografts - Khorki, M. Eyad; Shi, Tiffany; Cianciolo, Eileen E.; Burg, Ashley R.; Chukwuma, P. Chukwunalu; Picarsic, Jennifer L.; Morrice, Mary K.; Woodle, E. Steve; Maltzman, Jonathan S.; Ferguson, Autumn; Katz, Jonathan D.; Baker, Brian M.; et al. (Frontiers in Immunology, 2023)
Significant evidence suggests a connection between transplant rejection and the presence of high levels of pre-existing memory T cells. Viral infection can elicit viral-specific memory T cells that cross-react with allo-MHC capable of driving allograft rejection in mice. Despite these advances, and despite their critical role in transplant rejection, a systematic study of allo-reactive memory T cells, their specificities, and the role of cross-reactivity with viral antigens has not been performed. Here, we established a model to identify, isolate, and characterize cross-reactive T cells using Nur77 reporter mice (C57BL/6 background), which transiently express GFP exclusively upon TCR engagement. We infected Nur77 mice with lymphocytic choriomeningitis virus (LCMV-Armstrong) to generate a robust memory compartment, where quiescent LCMV-specific memory CD8+ T cells could be readily tracked with MHC tetramer staining. Then, we transplanted LCMV immune mice with allogeneic hearts and monitored expression of GFP within MHC-tetramer defined viral-specific T cells as an indicator of their ability to cross-react with alloantigens. Strikingly, prior LCMV infection significantly increased the kinetics and magnitude of rejection as well as CD8+ T cell recruitment into allogeneic, but not syngeneic, transplanted hearts, relative to non-infected controls. Interestingly, as early as day 1 after allogeneic heart transplant an average of ~8% of MHC-tetramer+ CD8+ T cells expressed GFP, in contrast to syngeneic heart transplants, where the frequency of viral-specific CD8+ T cells that were GFP+ was <1%. These data show that a significant percentage of viral-specific memory CD8+ T cells expressed T cell receptors that also recognized alloantigens in vivo. Notably, the frequency of cross-reactive CD8+ T cells differed depending upon the viral epitope. Further, TCR sequences derived from cross-reactive T cells harbored distinctive motifs that may provide insight into cross-reactivity and allo-specificity. In sum, we have established a mouse model to track viral-specific, allo-specific, and cross-reactive T cells; revealing that prior infection elicits substantial numbers of viral-specific T cells that cross-react to alloantigen, respond very early after transplant, and may promote rapid rejection.